Predictors of stroke literacy among African Americans in the “buckle of the stroke belt” - Sunmonu, N. Abimbola; Malek, Angela M.; Jenkins, Carolyn; Hyacinth, Hyacinth I. (Frontiers in Stroke, 2024)
Background: Stroke is associated with racial disparities in morbidity and mortality and stroke outcomes. Stroke literacy is a significant predictor of on-time arrival to the emergency room for acute stroke treatment. In this study, we examined sociodemographic and socioeconomic factors that predict key aspects of stroke literacy: knowledge of stroke signs/symptoms and intent to call 911 in the event of a stroke.We analyzed archived data from a survey of African American adults over 18 years residing in the 'buckle of the stroke belt'. Participants were ranked into 2 categories: low or no and moderate to adequate stroke knowledge. Then we performed univariate and multivariable analyses to determine the independent predictors of (1) knowledge of stroke signs and symptoms and (1) intent to call 911.Results: Participants aged 18-39 years (OR=0.46, 95%CI: 0.27-0.80) were more likely to correctly recognize stroke signs and symptoms compared to those who are 65 years and above. Those age 40-64 years were also more likely to recognize stroke signs and symptoms compared to those who are 65 years and above. On the other hand, those with less than high school (OR = 2.83, 95% CI : 2.03-3.96) or complete high school education (OR = 1.95, 95% CI: 1.28-2.96) were less likely to recognize stroke signs and symptoms. Males were less likely (OR = 0.65, 95% CI: 0.64-0.66) to report that they would call 911 in the event of a stroke. While respondents aged 40-64 years (OR = 1.87, 95% CI: 1.14-3.09) and those with moderate to adequate knowledge of stroke (OR = 1.39, 95% CI: 1.18-1.65) were more likely to call 911 in the event of a stroke. Socioeconomic status was generally associated with stroke literacy.Among resident of the "buckle of the stroke belt", we observed that age, sex, and educational level are among the key predictors of knowledge of stroke signs and symptoms and intent to call 911 in the event of a stroke. Stroke literacy and educational programs needs to incorporate these key sociodemographic aspects as a strategy for improving literacy and reduce stroke-related disability and health disparities.